The Original Text Form and Chapter Order of the Physiologus, with an Edition of the Chapter on the Lizard in Π - Macé, Caroline (Matenadaran, 2024)
Abstract The oldest textual form of the first recension of the Physiologus can be reconstructed thanks to a precise comparison between the Armenian translation, Latin translation y, and one single Greek manuscript, Π (Moscow, GIM, Sinod. Gr. 467). The strange placement of the chapter on the lizard at the beginning of the collection in both Π and the Armenian translation can be explained by assuming a codicological accident in their common ancestor. The chapter on the lizard is the last in the collection in the Latin version y of the Physiologus and the model of the Physiologus syrus Leidensis, and this must have been its original position. The folio on which that chapter was written fell off and was wrongly put at the beginning rather than the end of the book in the ancestor of Π and the Armenian version. The placement of the lizard in the second position, as in the majority of Greek manuscripts, can be interpreted as an attempt at correcting the misplacement that had occurred in the model of Π. In accordance with that hypothesis, all Greek manuscripts (except Π) and the Ethiopic translation as well as Latin x depend upon a unique hyparchetype. This conclusion completely changes our views on the textual history of the Physiologus.
Keywords: Greek